SINGLE-DOSE PHARMACOKINETIC STUDY OF CIPROFLOXACIN AFTER ORAL ADMIN- ISTRATION TO THE HEALTHY FEMALE VOLUNTEERS - Bashir, Farzana; Nawaz, Muhammad; Nawaz, Rakshanda; Ijaz, Ishrat (Biological Sciences - PJSIR, 2004)
The disposition kinetic of ciprofloxacin was evaluated in 10 adult healthy female volunteers. Appropriate mathematical model was applied for the estimation of the basic pharmacokinetic parameters because the statistical tests and profiles formed the basis for accepting or rejecting a proposed model. After single oral dose of 500 mg ,the blood samples were collected and ciprofloxacin concentrations were determined in serum by High Performance Liquid Chromatography. The mean value of plasma elimination half life (t ½) was estimated as 4.08 ± 1.3 h, maximum plasma concentration (C max) was 1.56 ± 0.49 mg/l obtained at mean value of ( Tmax) 2.11 ± 1.9 h. The average value of area under the curve was 8.96 ± 7.70 h-mg/l and is calculated from to to ta, while the average absorption rate constant was 1.56 ± 1.84 l/h. The average value for clearance was 78.08 ± 41.36 l/h. Volume of distribution and mean resident time showed an average value of 197.0 ± 98.88 litre and 4.82 ± 4.22 h, respectively. There was a significant deviation from the literature trends in respect to Vd and clearance.So this study supports the need for comprehensive evaluation of drug under indigenous conditions to obtain pharmacokinetic parameters on which the rational dosage regimens of drug could be based.